Oxidized lipoproteins are associated with markers of inflammation and immune activation in HIV-1 infection. (13th November 2016) - Kelesidis, Theodoros; Jackson, Nicholas; McComsey, Grace A.; Wang, Xiaoyan; Elashoff, David; Dube, Michael P.; Brown, Todd T.; Yang, Otto O.; Stein, James H.; Currier, Judith S.
Abstract : Objective: The pathogenesis of immune dysfunction in chronic HIV-1 infection is unclear, and a potential role for oxidized lipids has been suggested. We hypothesize that both oxidized HDL and LDL (HDLox and LDLox ) contribute to HIV-1-related immune dysfunction. Study: In the AIDS Clinical Trials Group A5260, 234 HIV-infected antiretroviral therapy (ART)-naive participants were randomized to receive tenofovir–emtricitabine and protease inhibitors or raltegravir and had HIV-1 RNA less than 50 copies/ml by week 24 and thereafter. Methods: Associations between biomarkers of inflammation (IL-6, high-sensitivity C-reactive protein and D-dimer), immune activation (sCD163, sCD14, soluble IL-2 receptor, CD38 and HLA-DR), inflammatory monocytes (CD14 + CD16 + ), T-cell senescence (CD28 and CD57) and exhaustion (PD1), and HDLox, LDLox were assessed at entry and after ART (week 96) with Spearman (partial) correlations. Results: HDLox declined and LDLox increased over 96 weeks of ART. Positive associations were observed at baseline and over time between HDLox (but not consistently for LDLox ) and most markers of inflammation and immune activation (but not senescence/exhaustion), even after adjustment for multiple comparisons, demographics, entry CD4 + cell count and HIV-1 RNA. HDLox was positively associated with IL-6 ( r = 0.19 − 0.29, P < 0.01) and sCD163 ( r = 0.14 − 0.41, P ⩽ 0.04) at all time points. Conclusion: These prospective longitudinal data suggest that oxidized lipoproteins may contribute to persistent immune activation on ART. Abstract : Supplemental Digital Content is available in the text